Conservation programme of the Spanish pig genetic resources - Delgado J.V.; Barba C.; Poto A.; Sánchez L.; Calero R.; Fresno M. (Tradition and innovation in Mediterranean pig production, 2000)
The aim of this paper is to describe a project for the conservation of native Spanish pigs genetic resources developed in five objective 1 Spanish regions. The following breeds are involved in this project: Chato Murciano, Celta, Negro Canario and several varieties of the Iberian Branch. Only the Negro Mallorquin could not be taken into account because it is located in objective 2 regions. The topics of this program were focused on three different subjects: collection and updating of information about the present status of these breeds; morphologic, productive and genetics characterization and, finally, the creation of a duplicated frozen semen bank. This paper describes the organization of the project and its present situation.
4. International Symposium on Mediterranean Pig, 1998/11/26-28, Evora (Portugal)